2023
DOI: 10.3390/app13084934
|View full text |Cite
|
Sign up to set email alerts
|

Improving Soil Stability with Alum Sludge: An AI-Enabled Approach for Accurate Prediction of California Bearing Ratio

Abstract: Alum sludge is a byproduct of water treatment plants, and its use as a soil stabilizer has gained increasing attention due to its economic and environmental benefits. Its application has been shown to improve the strength and stability of soil, making it suitable for various engineering applications. However, to go beyond just measuring the effects of alum sludge as a soil stabilizer, this study investigates the potential of artificial intelligence (AI) methods for predicting the California bearing ratio (CBR)… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 80 publications
0
4
0
Order By: Relevance
“…The realm of geotechnical engineering, while somewhat reserved in its adoption of AI, has begun to witness the application of AI-based techniques in addressing complex challenges. AI methods such as artificial neural networks (ANNs), fuzzy inference systems (FISs), adaptive neuro-fuzzy inference systems (ANFISs), and others have shown remarkable potential in deciphering intricate relationships within complex datasets across diverse domains such as soil dynamics [15][16][17][18][19][20], deep foundations [21][22][23][24], soil cracking [25][26][27], recycled materials [28][29][30][31][32][33][34][35][36], soil mechanics [37,38], tunnelling and rock mechanics [39][40][41] and other fields [42][43][44][45][46][47][48][49][50][51]. The beauty of these techniques lies in their capacity to capture nonlinear interactions between a myriad of variables, even when the underlying relationships are not fully understood.…”
Section: Introductionmentioning
confidence: 99%
“…The realm of geotechnical engineering, while somewhat reserved in its adoption of AI, has begun to witness the application of AI-based techniques in addressing complex challenges. AI methods such as artificial neural networks (ANNs), fuzzy inference systems (FISs), adaptive neuro-fuzzy inference systems (ANFISs), and others have shown remarkable potential in deciphering intricate relationships within complex datasets across diverse domains such as soil dynamics [15][16][17][18][19][20], deep foundations [21][22][23][24], soil cracking [25][26][27], recycled materials [28][29][30][31][32][33][34][35][36], soil mechanics [37,38], tunnelling and rock mechanics [39][40][41] and other fields [42][43][44][45][46][47][48][49][50][51]. The beauty of these techniques lies in their capacity to capture nonlinear interactions between a myriad of variables, even when the underlying relationships are not fully understood.…”
Section: Introductionmentioning
confidence: 99%
“…Machine learning has been widely applied in many fields of science and engineering, including geotechnical engineering. Several studies have demonstrated the effectiveness of machine learning in predicting various properties in geotechnics, such as soil dynamics [36][37][38][39][40][41][42][43][44], slope stability, and soil cracking [45][46][47][48][49][50][51][52]. A comprehensive study has not yet been presented on the use of artificial intelligence models to predict the thermal conductivity of sand.…”
Section: Introductionmentioning
confidence: 99%
“…A method that was successfully used in various fields of geotechnical engineering and has shown acceptable results is artificial intelligence [45]. Over the past two decades, artificial intelligence methods have been applied successfully in a wide range of geotechnical engineering disciplines, including soil dynamics [46][47][48], slope stability [49][50][51][52], fracture mechanics [53][54][55][56], rock and tunnel mechanics [57][58][59][60][61][62], among others. However, no studies have been published on the application of artificial intelligence methods to predict the friction angle of sand-rubber mixtures.…”
Section: Introductionmentioning
confidence: 99%